Occupational Therapy Therapeutic and Creative Use of Activity - Huri, Meral (IntechOpen, 2018)
Occupational therapy is a health care specialty with a deep focus on client-centered and holistic rehabilitation to improve the individual's occupational performance, quality of life and well-being through participation in meaningful and purposeful activities. This new book presents the importance of the therapeutic and creative use of activity in different populations, which is one of the core components of occupational therapy. Rehabilitation, rehabilitation delivery and outcomes are affected by recent changes in the meaning of health and social values. This resulted in an increasing necessity for therapeutic therapy, as well as creative use of activity in occupational therapy. This book focuses on recent advances in occupational therapy and reviews current practical guidelines. It introduces updated knowledge and skills for children, adults and the communities, including physical, mental, social, sensory, behavioral, environmental and community-based interventions to prevent, promote and improve activity use. The book will be relevant to occupational therapists, speech and language therapists, physical therapists, psychiatrists, psychologists, social workers and all the members of interdisciplinary rehabilitation team care workers.